(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aimed to identify the Sociocultural factors (student personal factors, factors related to the family, and factors related to community) that are related to the phenomenon of school violence among high school students in Irbid and Bani Obaid district in north of Jordan, the sample consisted of (312) male and female students who are registered in the academic year 2022/2023. A self-reported Questionnaire was distributed using Google forms using snow ball sampling method, data collected From October 2022 to the end of November 2022. The questionnaire was designed and modified by researcher, included ( 30 ) paragraphs containing the factors related to school violence, divided into three areas; The first field: student Personal factors and contains (9) paragraphs, and the second field: factors related to family, and contains (10) paragraphs, and the third field: factors related to community, and contains (11) paragraphs. The results showed that the “student personal factors” came in the first place as the highest related factor to scool violence (M=3.86, SD=0.82), and the factors related to Family came in the second place (M=3.69, SD=0.77 ), and in the last place the factors related to the community mean of (M=3.32, SD= 0.67) was moderately related to school violence. In recommendation: a diverse educational environment, and increasing school activities, and increase participation of parents in evaluating and correcting students who are involved in violent practices to reduce school violence.